PENGARUH KARAKTERISTIK KOMITE AUDIT : UKURAN, RAPAT, KOMITE AUDIT INDEPENDEN, DAN AUDIT COMMITTEE FINANCIAL EXPERTISE TERHADAP AUDIT REPORT LAG DENGAN COST OF DEBT SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan yang terdaftar Di Bursa Efek Indonesia Tahun 2015-2019) - Vebriane Werdaningrum; Herry Laksito (Diponegoro Journal of Accounting, 2021)
This study aims to discuss the effect of audit committee characteristics on size, meetings, independent audit committees, and audit committee financial expertise on audit report lag with cost of debt as moderating variables in developing countries. The variables used in this study are dependent variables (delay in audit reports), independent variables (size of audit committees, audit committee meetings, independent audit committees, and audit committee financial expertise), moderation variables (cost of debts).The population in this study is all companies listed on the Indonesia Stock Exchange in 2015-2019 except financial companies. Sampling is done by purposive sampling. Based on purposive sampling method, samples obtained by 58 companies for five consecutive years (2015-2019). The method of analysis used in this study is multiple regression analysis. In addition, the statistical techniques used to test the hypotheses proposed in this study are panel data.The results of this study indicate that the size of the audit committee and audit committee financial expertise have no significant effect on audit report lag. While, the independence of audit committees and audit committee meetings have a significant effect on audit report lag and debt costs strengthens the relationship between the size, expertise of the audit committee, and the independence of the audit committee.